Efficacy of radiation plus transarterial chemoembolization and lenvatinib in hepatocellular carcinoma with portal vein tumor thrombus - Dong, Aoran; Zhu, Meiyan; Zhang, Zeyu; Fan, Wenzhe; Wu, Zhiqiang; Chen, Yong; Tu, Jianfei; Zhang, Yaojun; Zhuang, Wenquan; He, Xiaofang; Peng, Zhenwei (Frontiers in Oncology, 2023)
Background We aimed to investigate the efficacy of a novel regimen, external beam radiation (RT) combined with trans arterial chemoembolization (TACE) and lenvatinib (LEN), in the treatment of hepatocellular carcinoma (HCC) with portal vein tumor thrombus. Methods We prospectively observed 102 participants from three tertiary medical centers in China between October 2018 and October 2020, who chose either RT plus TACE and LEN (RT-TACE-LEN) or TACE and LEN (TACE-LEN). LEN (12 mg or 8 mg daily) was administrated orally and continued until progression or intolerable side effects were noted. TACE was given one day after administration of LEN, and RT began within 4 weeks after the first TACE. The median dose/fraction of RT was 50 Gy/25 fractions (range: 45-60 Gy/25 fractions). Overall survival and progression free survival were compared between two groups, and complications were assessed. Results Both 51 patients received RT-TACE-LEN and TACE-LEN, respectively. Most patients had tumor size> 5 cm (73.8%) and tumor number≥ 2 (69.9%). The overall incidence of toxicities was significantly higher in RT-TACE-LEN group than TACE-LEN group (100% vs. 64.7%, p< 0.001), but incidences of grade 3-4 toxicities were comparable (54.9% vs. 49.0%, p= 0.552). Both median overall survival (22.8 vs. 17.1 months, p= 0.031) and median progression-free survival (12.8 vs. 10.5 months, p= 0.035) were significantly longer after RT-TACE-LEN treatment than TACE-LEN. Conclusions The addition of RT to TACE and LEN was safe, and might improve clinical outcomes of patients with advanced HCC, which needs conformation from further studies.